Managerial discretion and efficiency of internal capital markets - Iskenderoglu, Cansu (Journal of Corporate Finance, 2021)
I use the staggered adoption of state-level antitakeover laws to provide causal evidence that managerial agency problems reduce the allocative efficiency of conglomerate firms. I find that increases in control slack following the passage of antitakeover laws reduces q-sensitivity of investment by 64%. The adverse impact of the laws appears mostly at conglomerate firms that benefited from disciplinary takeover threats prior to the passage of the laws, lacked alternative sources of pressure on management, or had the structural makings to fuel wasteful influence activities and power struggles among managers. These findings suggest that takeover threats impact the efficiency of resource allocation.